Investigating Labrador Sea's persistent surface O2 anomaly using observations and biogeochemical model results - Amavi N. Silva; Duncan A. Purdie; Nicholas R. Bates; Toby Tyrrell (Journal of Marine Systems, 2024)

Geographical CO 2 sensitivity of phytoplankton correlates with ocean buffer capacity - Sophie Richier; Eric P. Achterberg; Matthew P. Humphreys; Alex J. Poulton; David J. Suggett; Toby Tyrrell; Christopher Mark Moore (Global Change Biology, 2018)
Accumulation of anthropogenic CO 2 is significantly altering ocean chemistry. A range of biological impacts resulting from this oceanic CO 2 accumulation are emerging, however, the mechanisms responsible for observed differential susceptibility between organisms and across environmental settings remain obscure. A primary consequence of increased oceanic CO 2 uptake is a decrease in the carbonate system buffer capacity, which characterizes the system's chemical resilience to changes in CO 2 , generating the potential for enhanced variability in p CO 2 and the concentration of carbonate [ ], bicarbonate [ ], and protons [H + ] in the future ocean. We conducted a meta‐analysis of 17 shipboard manipulation experiments performed across three distinct geographical regions that encompassed a wide range of environmental conditions from European temperate seas to Arctic and Southern oceans. These data demonstrated a correlation between the magnitude of natural phytoplankton community biological responses to short‐term CO 2 changes and variability in the local buffer capacity across ocean basin scales. Specifically, short‐term suppression of small phytoplankton ( p CO 2 within experiments performed in regions with higher ambient buffer capacity. The results further highlight the relevance of phytoplankton cell size for the impacts of enhanced p CO 2 in both the modern and future ocean. Specifically, cell size‐related acclimation and adaptation to regional environmental variability, as characterized by buffer capacity, likely influences interactions between primary producers and carbonate chemistry over a range of spatio‐temporal scales.

The influence of lithogenic material on particulate inorganic carbon measurements of coccolithophores in the Bay of Biscay - Chris J. Daniels; Toby Tyrrell; Alex J. Poulton; Laura Pettit (Limnology and Oceanography, 2012)
Following earlier data suggesting a decoupling between coccolithophore abundance and its suggested proxy, particulate inorganic carbon (PIC), we investigated this relationship in the Bay of Biscay (northwest European shelf), between December 2009 and July 2010. Coccolithophore abundance, coccolith calcite, and PIC were determined in surface waters (5‐m depth) along a transect crossing the Bay. Emiliania huxleyi was the most abundant species of coccolithophore and the main contributor of coccolith calcite (55–64%). PIC ranged from 0.07 to 11.7 mmol C m −3 , and coccolith calcite from 0.002 to 0.27 mmol C m −3 . Total PIC exceeded coccolith calcite in all samples, with only ∼ 11% of the PIC attributed to coccoliths. Coccolithophores alone could not account for the PIC concentrations measured. Lithogenic particulate matter, with calcite and dolomite components, was observed in samples across the route and decoupled the relationship between PIC and coccolithophore abundance. Presence of lithogenic material and Mesozoic fossil coccoliths in the samples implies sediment resuspension. These findings question the suitability of PIC as a proxy for coccolithophore abundance and dynamics, particularly on or near continental shelves, where the resuspension and lateral transport of lithogenic calcite may decouple the potential relationship between PIC and coccolithophores.

Nitrate : phosphate ratios and Emiliania huxleyi blooms - Evelyn J. Lessard; Agostino Merico; Toby Tyrrell (Limnology and Oceanography, 2005)
It has been hypothesized that phosphate limitation, classically indicated by NO 3 : PO 4 ratios >16, is one of the critical factors allowing the coccolithophorid Emiliania huxleyi to bloom. This hypothesis is based on physiological studies showing that E. huxleyi has an exceptionally high affinity for orthophosphate and is able to use organic phosphate. Indeed, E. huxleyi has been found to bloom at high NO 3 : PO 4 ratios in some mesocosm studies and in the oceanic northeast North Atlantic. Recent E. huxleyi blooms on the southeastern Bering Sea shelf, however, occurred under low NO 3 : PO 4 conditions, which is indicative of nitrogen rather than phosphorus stress. A review of field studies of blooms where nitrate and phosphate were measured indicates that NO 3 : PO 4 was in fact frequently low. A survey of most of the areas of the world ocean where satellite‐detected E. huxleyi blooms occur also shows that NO 3 : PO 4 ratios are generally low. These observations suggest that E. huxleyi is able to exploit situations where either phosphorus or nitrogen is limiting to competing species. They also indicate that attention should be directed to examining organic nitrogen, organic phosphorus, and ammonium during E. huxleyi blooms to better understand the role macronutrients play in these blooms.